(untitled) (Global Journal of Human-Social Science, 2023)
The publication of the Arbitration Act No 2 of 2017 as the first law on independent and special arbitration is one of the most important complementary laws for the investment climate in order to develop national legislation and keep pace with globalization in order to create a stimulating business and investment environment to attract and encourage foreign investment attract prestigious and international arbitration centers to benefit from arbitration law and open branches in Qatar